Pengaruh Digital Marketing dan Kualitas Produk Terhadap Keputusan Pembelian Produk Arj88 Store - I Komang Pande Wiratama; Komang Krisna Heryanda; Fridayana Yudiaatmaja (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
Rapid technological developments encourage entrepreneurs to utilize digital media in marketing to expand market reach and increase sales because many consumers have switched to digital purchases. This study aims to examine the influence of digital marketing and product quality on purchasing decisions at the Arj88 Store in Singaraja City. Quantitative research with a causal associative approach was chosen as the research method. The study involved 180 consumers who had purchased fashion products at the Arj88 Store, selected using a purposive sampling technique. Data were collected through online questionnaires and analyzed using multiple linear regression using SPSS. The study shows that digital marketing and product quality simultaneously have a positive effect on purchasing decisions, and partially, both digital marketing and product quality have a positive effect on purchasing decisions. Marketing strategies through digital media can increase consumer interest in making purchases. Product quality such as material, design, and neatness have a significant influence on purchasing decisions. The effectiveness of digital marketing and good product quality have been proven to increase consumer confidence in purchasing products. The implication of this research is that Arj88 Store is expected to continue to improve quality and create interesting content and collaborate with influencers to increase consumer reach and check product quality before giving it to consumers.